CONCEPTUAL FRAMEWORK FOR INTEGRATED SUSTAINABLE MANAGEMENT OF SOILS AND BOTTOM SEDIMENTS - Rudenko, Dariia; Kucher, Anatolii (Journal of Agricultural Sciences (Belgrade), 2025)
This study explores a sustainable framework for bottom sediment management, utilizing both SWOT and PESTEL analyses to assess its strategic viability. Through structured evaluations, the study identifies key strengths, including the circular economy benefits of sediment reuse, job creation potential, and improvements in soil fertility. However, challenges such as contamination, regulatory compliance, and logistical costs are also highlighted as factors that need careful management. The PESTEL analysis reveals strong external support in the form of favorable environmental and regulatory conditions, while the SWOT analysis provides a positive strategic potential score, indicating a feasible path forward. Additionally, the study addresses the role of sediment management in post-war recovery, particularly relevant for areas in Ukraine, suggesting its application for landscape restoration and infrastructure reinforcement. By integrating both internal and external factors, this research offers a comprehensive model for sediment repurposing, supporting sustainable development goals in resource management, environmental protection, and agricultural productivity. The results emphasize the potential of applying sustainable sediment management practices in the agricultural sector to support sustainable development. Key words: sustainable sediment management, agricultural waste reuse, environmental resource management, circular economy in agriculture, remediation techniques, bioremediation in agriculture, post-war environmental recovery, bottom sediment recycling.